Alterations in Gut Microbiota Composition Are Associated with Changes in Emotional Distress in Children with Obstructive Sleep Apnea - Chung-Guei Huang; Wan-Ni Lin; Li-Jen Hsin; Yu-Shu Huang; Li-Pang Chuang; Tuan-Jen Fang; Hsueh-Yu Li; Terry B. J. Kuo; Cheryl C. H. Yang; Chin-Chia Lee; Li-Ang Lee (Microorganisms)
Emerging evidence underscores the pivotal role of the gut microbiota in regulating emotional and behavioral responses via the microbiota–gut–brain axis. This study explores associations between pediatric obstructive sleep apnea (OSA), emotional distress (ED), and gut microbiome alterations before and after OSA treatment. Sixty-six children diagnosed with OSA via polysomnography participated, undergoing adenotonsillectomy alongside routine educational sessions. ED was assessed using the OSA-18 questionnaire, categorizing participants into high ED (scores ≥ 11, 52%) and low ED (scores < 11, 48%) groups. Gut microbiome analysis revealed significant diversity differences, with high ED linked to a reduced Shannon index (p = 0.03) and increased beta diversity (p = 0.01). Three months post-treatment, significant improvements were observed in OSA symptoms, ED scores, and gut microbiome alpha diversity metrics among 55 participants (all p < 0.04). Moreover, changes in the relative abundances of Veillonella, Bifidobacterium, Flavonifractor, and Agathobacter, as well as ultra-low frequency power and low frequency power of sleep heart rate variability, were independently associated with ED score alterations. These findings underscore the gut microbiome’s critical role in the emotional and behavioral symptoms associated with pediatric OSA, suggesting that microbiome-targeted interventions could complement traditional treatments for ED reduction and emphasizing the need for further research.